2005
DOI: 10.1248/bpb.28.1385
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cisplatin or Nedaplatin-Induced Nephrotoxicity and Renal Accumulation

Abstract: Nedaplatin is known to exhibit antitumor activity similar to that of cisplatin. However, concerning side effects, nedaplatin causes renal toxicity less frequently than cisplatin. In this study, we compared the incidence of renal toxicity between cisplatin and nedaplatin by investigating the difference in kidney tissue accumulation. Kidney tissue accumulation of cisplatin administered at 3.75 mg/kg was similar to that of nedaplatin administered at 24 mg/kg. At these doses, the plasma creatinine level and urinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 19 publications
(15 reference statements)
2
40
0
Order By: Relevance
“…It has also been reported that cisplatinrelated nephrotoxicity develops in a dose-dependent manner in animals and humans. [30] In animal models, the S3 segment of the proximal tubule appears to be major site of renal injury. [2,18,29,31] In humans, however, damage seems to occur primarily in the distal tubule and collecting ducts.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that cisplatinrelated nephrotoxicity develops in a dose-dependent manner in animals and humans. [30] In animal models, the S3 segment of the proximal tubule appears to be major site of renal injury. [2,18,29,31] In humans, however, damage seems to occur primarily in the distal tubule and collecting ducts.…”
Section: Discussionmentioning
confidence: 99%
“…Kawai et al 27 showed that renal accumulation of platinum when cisplatin was administered at 3.75 mg/kg was similar to that of NDP administered at 24 mg/kg, and that both drugs at these two doses induced similar effects in the kidney. It was inferred, therefore, that the nephrotoxicity of NDP was lower than that of CDDP due to lower accumulation of platinum.…”
Section: ##mentioning
confidence: 99%
“…Nedaplatin is a derivative of second-generation platinum that has similar antitumor activities to Multi-institutional prospective study of nedaplatin plus S-1 chemotherapy in recurrent and metastatic nasopharyngeal carcinoma patients after failure of platinum-containing regimens cisplatin with less gastrointestinal toxicity and nephrotoxicity [Kawai et al 2005;Sasaki et al 1991;Alberts et al 1997]. Also, our recent phase II study of nedaplatin plus capecitabine has shown satisfactory antitumor activity as salvage chemotherapy for cisplatin-refractory recurrent and metastatic NPC [Peng et al 2013].…”
Section: Introductionmentioning
confidence: 99%